PENGAWASAN TERHADAP PEDAGANG KAKI LIMA DALAM MENERTIBKAN OBJEK WISATA PANTAIPURUS KOTA PADANG - Pertiwi, Dian; Achnes, Sofia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Purus beach is a bustling tourist attraction on the visit of tourists. Same is the case with othertourist attractions, it's only natural when coastal sights Purus demand by street vendors who holdcommodities around the area. Street vendors appear as secondary economic and population demandsto meet daily needs. Local people saw this as an opportunity for them to do business, because this areahas a high enough potential trade and does not require a high relative capital. Many street vendorsdisturb public order and peace of the community because of the many merchants who violate the rulesset. This research aims to know the Scrutiny Against street vendors In Coastal Sights Regulate PurusPadang city and the factors that affect any such Scrutiny. The concept of theory that researchers use isthe concept of supervision according to the Brantas. Indicators in this research that preventivesurveillance, process and repressive. This research uses qualitative research methods, theresearchers filmed research in the Beach City of The purus. Research using informants as adata source with data collection techniques with observation, documentation and interviews.Based on real research, implementation of the supervision of street vendors has been done,but still a lack of awareness of the trader in complying with regulations, sanctions given havenot posed a deterrent effect for merchants and still found weaknesses in the form factor of thehuman resources and facilities and infrastructure that is owned by satpol pp.keywords: supervision, curbing, preventive, process, and repressive